2020
DOI: 10.1002/emp2.12261
|View full text |Cite
|
Sign up to set email alerts
|

A teenager with fever, chest pain, and respiratory distress during the coronavirus disease 2019 pandemic: a lesson on anchoring bias

Abstract: Symptoms of coronavirus disease 2019 overlap with other important illnesses affecting young adults. We report a case of a 17‐year old male presenting to the emergency department in the midst of a pandemic with symptoms of coronavirus disease 2019. He had fever, dyspnea, chest pain, and myalgias, with bilateral infiltrates on chest radiograph, and developed septic shock secondary to infectious thromboembolic events. However, his blood cultures grew group G streptococcus secondary to his oropharyngeal infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Tis perspective is also refected in the only retro-perspective study available that studied about 700 cases of LS from 2000 to 2017 and concluded that there are no disease-specifc elements of concern regarding the safety of anticoagulation in LS [12]. From our analysis of 26 LS cases from 2016 to 2021, anticoagulation was used in 76% of cases and the average duration was 9.8 weeks (ranging from 1 week to 16 weeks; Table 2 [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][41][42][43][44]. In our case, due to the absence…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Tis perspective is also refected in the only retro-perspective study available that studied about 700 cases of LS from 2000 to 2017 and concluded that there are no disease-specifc elements of concern regarding the safety of anticoagulation in LS [12]. From our analysis of 26 LS cases from 2016 to 2021, anticoagulation was used in 76% of cases and the average duration was 9.8 weeks (ranging from 1 week to 16 weeks; Table 2 [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][41][42][43][44]. In our case, due to the absence…”
Section: Discussionmentioning
confidence: 84%
“…Regarding the duration of antibiotics, Riordan, 2007, referenced an estimate of 9 to 84 days with an average of 42 days [2]. We have analyzed 26 cases of LS from 2016 to 2021, and the average antibiotics duration was 5.3 weeks (Table 2) [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][42][43][44]. In clinical practice, due to the lack of an established guideline, the duration and selection of antibiotics highly varied based on clinical responses in patients.…”
Section: Discussionmentioning
confidence: 99%
“…When symptoms are compatible with a current global pandemic virus, it is difficult to identify the real underlying cause without adequate diagnosis testing, and it is critical to rule out alternative possibilities [ 8 , 20 ].…”
Section: Discussionmentioning
confidence: 99%